2019
DOI: 10.1891/1058-1243.28.2.68
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Birth Practice #1: Let Labor Begin on Its Own

Abstract: As cesarean rates have climbed to almost one-third of all births in the United States, current research and professional organizations have identified letting labor begin on its own as one of the most important strategies for reducing the primary cesarean rate. At least equally important, letting labor begin on its own supports normal physiology, prevents iatrogenic prematurity, and prevents the cascade of interventions caused by labor induction. This article is an updated evidence-based review of the "Lamaze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…14 The most convincing reason to let labour begin on its own is the activation and stimulation of hormones like oxytocin, endorphins, catecholamines, and prolactin which regulate labour and birth. 15 The present study adds to the evidence that the odds of a natural onset of labour in the intervention group was 2.192 times more when compared to the standard care group with a 95% confidence interval [1.31-3.36], p<.001. Various other studies have shown that beta-endorphin levels were high after exercise (p <.001), which is necessary for the spontaneous onset of labour, 16 and exercise during labour excited uterine contraction.…”
Section: Discussionmentioning
confidence: 57%
“…14 The most convincing reason to let labour begin on its own is the activation and stimulation of hormones like oxytocin, endorphins, catecholamines, and prolactin which regulate labour and birth. 15 The present study adds to the evidence that the odds of a natural onset of labour in the intervention group was 2.192 times more when compared to the standard care group with a 95% confidence interval [1.31-3.36], p<.001. Various other studies have shown that beta-endorphin levels were high after exercise (p <.001), which is necessary for the spontaneous onset of labour, 16 and exercise during labour excited uterine contraction.…”
Section: Discussionmentioning
confidence: 57%
“…The latter consideration constitutes the most critical element in decision making, and thus, low-risk women who are, for any reason, opposed to early delivery at 39 weeks' gestation should be fully supported with expectant management. 22 In fact, some hospitals even in high-resource settings may not be able to provide labor induction for 39 weeks' gestation to all low-risk women within their jurisdiction. Nevertheless, from a scientific inference standpoint, the evidence shows that labor induction at 39 weeks' gestation prevents the progressively increasing risk of complications that pregnancies accrue, and this justifies the obstetrical indication of "labor induction for 39 weeks' gestation."…”
Section: Discussionmentioning
confidence: 99%
“…Some women and healthcare providers who advocate for physiological childbirth believe that labor induction among low-risk nulliparous women at 39 weeks' gestation increases rates of adverse perinatal outcomes compared with expectant management 21,22 (eg, they may believe the true RR to be 1.10, 1.20, or 1.50). Conversely, other clinicians and researchers may believe that such labor induction reduces adverse perinatal outcomes (eg, they may believe the true RR to be 0.70, 0.80, or 0.90).…”
Section: P Value Functionsmentioning
confidence: 99%
“…There is an increasing global commitment to respect the physiology of childbirth and adopt strategies to facilitate it, 1–3 including growing interest in ways to enhance physiologic birth, generally defined in research and health policy literature as a birth with no, or limited, clinical intervention 4 . Promoting physiologic birth aims to reduce the routine use of technology and interventions to manage pregnancy and childbirth, which is a global cause for concern 1,5 …”
Section: Introductionmentioning
confidence: 99%